The Influence of Competence, Work Environment and Work Family Conflict on Performance Mediated by Organizational Commitment (Survey of Public Junior High School Teachers in Kuningan Sub-District) - Sumi Krismiyati; Lili Karmela F; Dede Djuniardi (International Journal Labs, 2024)
The purpose of this study was to test and analyse the effect of competency, work environment and work family conflict on work performance mediated by organizational commitment (survey of public middle school teacher in Kuningan distric). The sampling technique used is probability sampling with simple random sampling approach and managed to acquire 161 sample comprised of teacher from public middle school in Kuningan. The technique used in this research wasinferential statistic with parametrich method and the tool used in this reseach is SmartPLS V.3,0 using SEM method. The result of this study shows that competency have positive and significant effect on organizational commitment, work environment have positive and significant effect on organizational commitment, work family conflict have positive but insignificant effect on organizational commitment and significant, competency have positive and significant effect on work performance, work environment have positive and significant effect on work performance, work family conflict have positive and significant effect on work performance, organizational commitment have positive and significant effect on work performance, organizational commitment can mediated the effect of competency on organizational commitment can mediate the effect of competency on work performance, organzational commitment can mediate the effect of work environment on performance, and organizational commitment cannot mediate the effect of work family conflict on performance.